2021
DOI: 10.1515/jbcpp-2020-0281
|View full text |Cite
|
Sign up to set email alerts
|

Cocos nucifera L. oil alleviates lead acetate-induced reproductive toxicity in sexually-matured male Wistar rats

Abstract: Objectives Lead primarily affects male reproductive functions via hormonal imbalance and morphological damage to the testicular tissue with significant alteration in sperm profile and oxidative markers. Though, different studies have reported that Cocos nucifera L. oil has a wide range of biological effects, this study aimed at investigating the effect of Cocos nucifera L. oil on lead acetate-induced reproductive toxicity in male Wistar rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…In the current study, LA-cessation rats (Group II(a)) showed reductions in SOD, CAT, GPx, and GSH activities and elevations in MDA concentration in tissue homogenates when compared with the untreated control rats. The present results agree with previous observations explaining that long-term exposure to lead causes oxidative damage by increasing lipid peroxidation (elevated MDA levels), inhibiting SOD, CAT, and GPX activity, and lowering GSH levels in the testes [10,34,5,35], reduced activities of antioxidant enzymes are frequently implicated in oxidative stress. Rats exposed to LA were reported to exhibit significantly lower levels of testicular antioxidant enzymes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, LA-cessation rats (Group II(a)) showed reductions in SOD, CAT, GPx, and GSH activities and elevations in MDA concentration in tissue homogenates when compared with the untreated control rats. The present results agree with previous observations explaining that long-term exposure to lead causes oxidative damage by increasing lipid peroxidation (elevated MDA levels), inhibiting SOD, CAT, and GPX activity, and lowering GSH levels in the testes [10,34,5,35], reduced activities of antioxidant enzymes are frequently implicated in oxidative stress. Rats exposed to LA were reported to exhibit significantly lower levels of testicular antioxidant enzymes.…”
Section: Discussionsupporting
confidence: 93%
“…Lead acetate is a bio-toxic industrial and environmental toxin found in almost all tissues in the body, including the liver, lungs, bones, kidneys, reproductive systems, and immune system [4]. Lead exposure has recently been identified as a significant cause of testicular dysfunction and male infertility [5]. The increased content of MDA is evidence of tissue damage produced by increased free radicals in lead poisoning mechanisms [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, exposure to PbAc resulted in a highly significant decrease in sperm count, motility, and viability compared to all the other investigated experimental groups, as well as a highly significant increase in sperm morphological abnormalities. Similar impaired semen parameters were previously reported in experimental animals exposed to PbAc [ 85 , 108 , 109 ]. Such an impairment might be attributed to the direct toxic effects of PbAc on sperm cells as well the enhanced production of ROS [ 31 ].…”
Section: Discussionsupporting
confidence: 89%
“…The caudal epididymis was dissected out, several incisions (1 mm) were made in the caudal epididymis, which was suspended in 1ml of Ham's f-10 solution after 3-5 minutes of incubation at 37 o C. The sperm swim up and the concentration and motility were determined by using new improved Neubauer Haemocytometer (Tang et al, 2003;Olaniyan et al, 2021b).…”
Section: Sperm Analysismentioning
confidence: 99%